Hubungan Aktifitas Fisik Dengan Tekanan Darah Pada Lansia Di Dusun Lendang Utama Desa Sesele Wilayah Kerja Puskesmas Gunungsari. - Nurul Ilmi; Antoni Eka Fajar Maulana; Eva Marvia (STIKES Mataram, 2022)
Physical activity is a movement of body that make muscle take out the energy. Lack of physical activity is the risky factor of chronic diseases and overall this is considered to make death in global. Elderly is a group of people in the last face of life. According to World Health Organisation (WHO) stated that middle age is in between 45- 59, elderly is in between 60-74, and those who are in above 90 year are considered too old.This research is aimed at determining the correlation between physical activity and blood pressure of elderly in Lendang Utama Sesela, The Working Area of Gunungsari Health Center. The research is quantitative study with analytic design using cross-sectional approach. The samples were all 72 elderly with hypertension from which 57 samples were selected through purposive sampling. The instruments of study are questionnaires and observation sheet.The research with Spearman rank showed that p-value > a (0.211 <0.05). This means that Ha is rejected and HO is accepted.It is inferred that there is correlation between physical activity and blood pressure of elderly in Lendang Utama Sesela, The Working Area of Gunungsari Health Center.Keywords: physical activity, elderly, blood pressure.